An obstacle in policymaking and evidence-based planning for enhancing education access to girls-A Comprehensive Analysis of Astonishing School Enrollment Case in Sindh-Pakistan - Ali, Sheraz; Sattar Shah, Syed Abdul; Sohoo, Muhammed Nawaz; Tagar, Abdul Karim; tagar, hamzo khan (Advances in Social Sciences Research Journal, 2020)
This Paper has been written in the above context to critically evaluate the Sindh school education enrollment data as a case study in details and suggests recommendation for improvement in data collections system particularly for policy planners in the greater public interest. It is scientific scrutiny of the data and valid for the researchers, decision-makers, development partners including donors and general readers as food for thought and net addition in the available literature on enrollment in the public sector schools.